2023
DOI: 10.1002/acr.25104
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Managing Nociplastic Pain in Individuals With Rheumatic Diseases: A Narrative Review

Abstract: Chronic pain is a burdensome and prevalent symptom in individuals with rheumatic disease. The International Association for the Study of Pain classifies pain into 3 descriptive categories: nociceptive, neuropathic, and nociplastic. These categories are intended to provide information about the mechanisms underlying the pain, which can then serve as targets for drug or non‐drug treatments. This review describes the 3 types of pain as they relate to patients seen by rheumatology health care providers. The focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…Of note, true arthritis may contribute to a proposed mechanism of FM development, as uncontrolled synovitis in the past, and ongoing inflammation may contribute to "bottom-up" sensitization, which refers to ongoing peripheral nociceptive pain signals facilitating and amplifying the pain response and ultimately leading to hypersensitivity and greater pain perception. 2 The increase in malar rash in patients with FM should be evaluated in larger cohorts and if an association is demonstrated, this could be due to more than one mechanism. The inflammation of cutaneous disease in SLE could contribute to peripheral sensitization of FM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, true arthritis may contribute to a proposed mechanism of FM development, as uncontrolled synovitis in the past, and ongoing inflammation may contribute to "bottom-up" sensitization, which refers to ongoing peripheral nociceptive pain signals facilitating and amplifying the pain response and ultimately leading to hypersensitivity and greater pain perception. 2 The increase in malar rash in patients with FM should be evaluated in larger cohorts and if an association is demonstrated, this could be due to more than one mechanism. The inflammation of cutaneous disease in SLE could contribute to peripheral sensitization of FM.…”
Section: Discussionmentioning
confidence: 99%
“…It is also pertinent for clinical trials assessing arthritis to not unintentionally enroll patients with noninflammatory arthralgia, perhaps accounting for increased response rates in standard of care placebo groups. Of note, true arthritis may contribute to a proposed mechanism of FM development, as uncontrolled synovitis in the past, and ongoing inflammation may contribute to “bottom‐up” sensitization, which refers to ongoing peripheral nociceptive pain signals facilitating and amplifying the pain response and ultimately leading to hypersensitivity and greater pain perception 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he presence of multiple bodily pain sites in patients undergoing TKA is known to be a strong prognostic indicator of poor outcome 11,13,32 . Chronic widespread pain, a characteristic of nociplastic pain 33 , was relatively common in our TKA sample (43% at baseline) and likely results from maladaptive changes to the nervous system leading to heightened central nervous system pain sensitivity 34,35 . In this secondary analysis of participants undergoing TKA and reporting moderate to high levels of pain catastrophizing, longitudinal data showed that bodily pain at sites beyond the surgically treated knee improved over the 1-year postoperative period.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings suggest a more targeted approach is necessary, focusing on biomarkers specific to the medical conditions associated with clinical pain. Chronic pain originates from various mechanisms— nociplastic, neuropathic, inflammatory, and nociceptive—each characterized by unique pathological features embedded in different bodily systems 9,24,25 . By concentrating on specific pain-related conditions, biomarkers can more accurately target these distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%